Drosaico, Marianorum Iudice - Đekić, Đorđe N.; Pavlović, Miloš N. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper tries to provide an answer to a question why a ruler of the Narentines was called a judge. When making a comparison between Drosaico and other occurrences of the title of judge at that time, it can be concluded that none of them was authorised to lead foreign policy. Such right was solely the ruler’s one. While researching why a ruler had a title of a judge, an interpretation suggests that at that time the ruler also became the supreme judge in the state and that that judicial authority was the most prominent one, hence the title. That information can be put into relation to the monk Simeon’s, the erstwhile a great mayor, Stefan Nemanja, Hilandar Charter where Rad‘s and George‘s judicature were mentioned. That meant that in this case the process of providing peace shifted from the social community to the Vlach elders as their supreme judges. However, it did not mean that the rulers or the Vlach elders adjudicated disputes but that they became the highest judicial instance.